INRUSH CURRENT OF LAMP (ETIMA, 2021)
AbstractLighting systems pass through big change in terms of light source recently. LED replace discharge lamp and thischange represent change of electrical parameters and influence to installations. Lighting systems with dischargelamp use inductive ballasts with choke and starter or electronic ballasts. Lamps with LED use drivers which areswitching sources. The drives include rectifier, high frequency oscillator, transformer and capacitors. Typically,rectifier has impact to distortion of luminaire current and capacitor has impact to inrush current. Over the lastyears, problem increases with inrush current. Public lighting networks reconstruct with LED luminaires. Oftenincrease inrush current and circuit-breaker must be changed for stronger. This change cause increasing ofpayment for energy distribution and sometime is necessary change installation. Aim of this paper is describedifference between luminaires from point of view inrush current. Size and duration of inrush current depends onconstruction of driver and on phase of supply voltage. In paper are analyzed amplitudes, durations and behaviorof electrical parameters various LED luminaires.Key wordsLED, lamp, driver, inrush current